1996
DOI: 10.1103/physrevb.53.11613
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic exchange-coupling effects in asymmetric trilayer structures of MBE-grown Co/Cr/Fe

Abstract: We present results of anisotropy and exchange-coupling studies of asymmetric Co/Cr/Fe trilayers and superlattices grown by molecular beam epitaxy on Cr͑001͒/Mg͑001͒ buffers and substrates. The magnetic properties have been investigated using both the longitudinal magneto-optical Kerr effect and ferromagnetic resonance. The hysteresis data obtained from the trilayer system were fit to a theoretical model which contains both bilinear and biquadratic coupling. The effective in-plane anisotropy was found to be of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The Nb/Fe bilayers on Al 2 0 3 (1120) substrates were prepared using a molecular beam epitaxy (MBE) system (for details about this equipment see, e.g., [12]). The vacuum base pressure of the machine is 5 • 10 -9 Pa, the working pressure is 2• 10 -8 Pa. Nb was evaporated by electron beam from a 14 em 3 crucible.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The Nb/Fe bilayers on Al 2 0 3 (1120) substrates were prepared using a molecular beam epitaxy (MBE) system (for details about this equipment see, e.g., [12]). The vacuum base pressure of the machine is 5 • 10 -9 Pa, the working pressure is 2• 10 -8 Pa. Nb was evaporated by electron beam from a 14 em 3 crucible.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Because of two equivalent {1 1 0} in-plane axes in Cr(0 0 1) two different Co(1 12 0) domains form with an angle of 90 • to each other. The thickness of the Cr interlayer between Co and Fe was chosen to be 3.1 nm to mediate a weak antiferromagnetic (AF) coupling as was found in [6]. The thicknesses of both magnetic layers (4.0 nm for Co and 3.0 nm for Fe) were chosen to be different due to their different magnetic moments and with the intention of a cancellation of the film magnetic moment in the antiparallel state of Co and Fe layer magnetization.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Furthermore, the fabrication of F 1 /N/F 2 type spin valves is easier than that of F/N/F/AF spin valves, as deposition of the AF layer can be dispensed. Co/Cr/Fe trilayers with thick Cr spacer layers have been shown in the past to be excellent examples for a spin valve type magnetization reversal [6], and the GMR effect has been determined by Buchmeier et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…9 This system is of interest due to demonstrated electrical spin injection from the Fe layer into GaAs and the presence of a coupled electronic-nuclear spin system found in GaAs. 8,10 In recent years, studies of Fe/Cr/Co structures deposited on MgO showed that the Co magnetization has fourfold-anisotropy 11 and provided evidence for both short and long period Cr thickness dependent oscillations. Further analysis in Ref.…”
mentioning
confidence: 99%